Peer-to-peer live video streaming on the internet issues, existing approaches, and challenges. - Bo Li; Hao Yin.
Live video streaming is perhaps the greatest unfulfilled promise of the Internet. There have been tremendous efforts in the design and experimentation of video-streaming systems in the past two decades; there have been no shortage of technical innovations, yet no single system has delivered the scale and service quality. The fundamental problem that throttles the large-scale deployment of Internet video streaming is the dissatisfaction end-users experience with performance. This is caused by a combination of many factors, such as the autonomous nature of the Internet, inherent instability, and lack of a service guarantee. This is further challenged by sustainable bandwidth and the stringent continuity requirements of streaming applications. Recent development of P2P-based streaming technology brings unprecedented new momentum to Internet video streaming, which has been shown to be cost-effective, scalable, and easy to deploy. This article reviews the state-of-the-art P2P live video-streaming technologies and their development from a historic perspective. Based on our earlier success with a large-scale P2P streaming system, Coolstreaming, we summarize the main innovations and discuss the key trade offs in the system design. We present our observations on the future development and offer a few insights for further discussion.
Keywords: Coolstreaming; Internet video streaming; P2P-based streaming technology; Inherent instability; Peer-to-peer live video streaming systems